Heparin Cofactor II Determination - Levels in Normals and Patients with Hereditary Antithrombin III Deficiency and Disseminated Intravascular Coagulation - Tran, Tri H; Duckert, F (Thrombosis and Haemostasis, 1984)
A technique is described to completely remove antithrombin III (AT) from small amounts of human plasma by immunoaffinity chromatography on antibodies against human AT linked to Sepharose 4B. The level of heparin cofactor II (HCII) was not affected by the immunoadsorption. HCII activity was then determined by measuring the rate of human thrombin inhibition by 3 ways: a) activation with heparin in AT-free plasma, b) activation with dermatan sulfate in normal plasma and c) activation with dermatan sulfate in AT-free plasma. The normal range of HCII varied between 0.7-1.5 U/ml, as compared to a normal plasma pool containing by definition 1 U/ml. Highly significant correlations between assays as obtained from 40 normal plasmas proved the suitability of the 3 assays, although the progressive thrombin inhibition by AT, when not removed, contributed about one fifth to the thrombin inhibition by HCII in the presence of dermatan sulfate. There were also highly significant correlations between HCII activity and antigen, as determined by rocket immunoelectrophoresis using specific antibodies against HCII.Levels of HCII and AT were examined in 7 patients with hereditary AT deficiency and 7 patients with disseminated intravascular coagulation (DIC). In hereditary AT deficiency, whereas the AT activity was reduced by half, levels of HCII activity and antigen were in the normal range. In DIC, a parallel decrease of HCII and AT suggests that HCII may participate in the inhibition of thrombin released during DIC and thus provides an inhibitor reserve, once the AT level becomes subnormally low.
Keywords: Heparin cofactor A; Antithrombin III; Disseminated intravascular coagulation; Antithrombin III deficiency; Immunoaffinity chromatography